From histology to sonography in skin and superficial tissue disorders: EURO-MUSCULUS/USPRM* approach - Ricci, Vincenzo; Ricci, Costantino; Cocco, Giulio; Donati, Danilo; Farì, Giacomo; Mezian, Kamal; Naňka, Ondřej; Özçakar, Levent (Pathology, research and practice, 2022)
BACKGROUND: In clinical practice, ultrasound assessment of the skin and superficial tissues is progressively becoming a valuable diagnostic tool to support physical examination in the outpatient setting. OBJECTIVES: The aim of this study was to define a standardized sonographic approach to (layer-by-layer) accurately evaluate multiple histological layers of the skin and superficial tissues. METHODS: Using high-frequency ultrasound probes and high-level ultrasound machines, we matched the histological microarchitecture of superficial tissues with multiple sonographic patterns in physiological and pathological conditions. Moreover, high-sensitive color/power Doppler assessments have also been performed to evaluate the microcirculation. RESULTS: Modern equipment allow for a detailed "sonographic dissection" of the skin and superficial tissues by evaluating different histological layers in various clinical scenarios. High-sensitive Doppler imaging clearly depicts the microvasculature, especially of pathologies. CONCLUSIONS: In clinical practice, using adequate technological equipment, a detailed sonographic assessment of the superficial (soft) tissues can be performed with the use of high-frequency B-mode and high-sensitive Doppler imaging.
Keywords: Dermis; Doppler; Ultrasonography; Muscles; Morphology; Histological Techniques; Subcutaneous fat; Ultrasound; lidé; histologické techniky; svaly; Skin; kůže; Humans; ultrasonografie